2022
DOI: 10.3390/ijms231710165
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PagSTOMAGEN, a Positive Regulator of Stomatal Density, Promotes Vegetative Growth in Poplar

Abstract: Poplar is an important fast-growing tree, and its photosynthetic capacity directly affects its vegetative growth. Stomatal density is closely related to photosynthetic capacity and growth characteristics in plants. Here, we isolated PagSTOMAGEN from the hybrid poplar (Populus alba × Populus glandulosa) clone 84K and investigated its biological function in vegetative growth. PagSTOMAGEN was expressed predominantly in young tissues and localized in the plasma membrane. Compared with wild-type 84K poplars, PagSTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…RT-qPCR assays were performed using TransStart Top Green qPCR SuperMix (TRANSGEN, China, Cat. AQ132-22) [ 50 ]. Three biological replicates were performed for each tissue.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR assays were performed using TransStart Top Green qPCR SuperMix (TRANSGEN, China, Cat. AQ132-22) [ 50 ]. Three biological replicates were performed for each tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of PdERECTA and PdEPFL6 also resulted in decreased stomatal density and increased drought tolerance without a significant reduction in biomass accumulation under non-limiting water conditions. However, when the positive regulator of stomatal development STOMAGEN was overexpressed in the poplar hybrid clone 84K, the plants displayed increased stomatal density and conductance, higher net photosynthetic rate, and higher vegetative growth [ 60 ]. In other cases, the complexity of the regulatory circuits involved in the control of stomatal differentiation makes it difficult to examine fully the effects of their perturbation [ 61 , 62 ].…”
Section: Identification Of Genes and Pathways Modulating Stomatal Dev...mentioning
confidence: 99%
“…Overall, published works suggest that reduction of stomatal density is a promising strategy for breeding or biotechnological programs aimed at obtaining drought resilient poplar genotypes [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, field-based trials remain desirable, as some observations made in natural conditions are not fully in agreement with those in confined environments.…”
Section: Identification Of Genes and Pathways Modulating Stomatal Dev...mentioning
confidence: 99%
“…The genes of the EPF / EPFL family indirectly affect stomatal development, for example EPFL9 positively regulates stomatal density, and EPF1 and EPF2 negatively regulate stomatal density. Studies have shown that as ligands, EPFL9 , EPF1 , and EPF2 can directly bind to receptors such as TMM/ERECTA (Hara et al ., 2007; Hunt & Gray, 2009; Lee et al ., 2015), thereby affecting the expression of downstream SPCH or MUTE (Pillitteri & Torii, 2012), and ultimately regulating stomatal development (Lee et al ., 2015; Xia et al ., 2022). A single ERECTA family (ERf) without a TMM recognize EPFL4 and EPFL6 of the EPF / EPFL family, and they can reduce stomatal density when combined with ERf receptors (Abrash et al ., 2011; Lin et al ., 2017; Jiao et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%